Makna Etis dan Estetis pada Tari Tradisional Aceh, Betawi, Bali, Kalimantan, Sulawesi, dan Papua - Wiradharma, Gunawan; Sediyaningsih , Sri; Prasetyo, Mario Aditya (PERSPEKTIF, 2024)
Discussions about ethical and aesthetic meaning in art, especially traditional dance will always be an interesting study to discuss amidst technological developments and globalization. This research aims to examine and describe the ethical, ethical, and aesthetic values of traditional Indonesian dance consisting of the regions of Aceh, Java, Kalimantan, Bali, Sulawesi, and Papua. The problem discussed in this research is what is the ethical and aesthetic meaning of traditional dance in Indonesia? This type of research is qualitative using a descriptive-analytical approach. The use of this qualitative method can provide more comprehensive knowledge results because it emphasizes process and meaning. Data collection in this research was carried out by interviews with dance maestros, cultural figures, choreographers, and dance academics. This research can provide a comprehensive understanding of the diversity of Indonesian traditional dance to expand the scope of knowledge of arts and culture. The results of this research show that traditional dances from the six selected regions have similarities in terms of geography, themes, and clothing. In general, the birth of traditional dance in these six regions was created from two regions, namely the coast and the mountains. Three big themes are usually raised in traditional dance, namely ritual, war, and entertainment. Clothing in the six selected regions has different characteristics. This difference has of course been regulated by the traditions and customs of the people who believe in it so that it becomes an ethic and aesthetic in a dance performance.